Parkinson's Elevated: improving healthspan - Kathleen E. McKee; Miriam R. Rafferty; Miriam R. Rafferty; Theadora W. Sakata; Theadora W. Sakata; Theadora W. Sakata; David M. Hedges; Garett J. Griffith; Maddison M. K. Bingham; Stephanie A. Obradovich; M. Nicholas Francis; Daniel M. Corcos (Frontiers in Sports and Active Living)
As Parkinson's disease (PD) progresses, relatively mild symptoms advance to a major disorder that affects every organ system in the body. Current care for people with PD (PwP) reacts to rising disability. There is a missed opportunity to keep PwP as healthy as possible. In this perspective, we spell out our vision for a proactive, value-based health care model built around a patient-centered integrated practice unit (IPU) for PD. The IPU will provide integrated interdisciplinary care overseen by a specialized Parkinson's primary care physician working closely with a movement disorders neurologist. The IPU will implement an evidence-based exercise program for people early in the disease. The focus of this intervention is a heart rate driven high-intensity aerobic exercise program, which is the only treatment with evidence that it can slow disease progression. It will also include resistance exercises, flexibility exercise and balance exercise. For people whose disease is moderate or severe, the IPU will provide care curated through a network of rehabilitation providers with expertise in PD all of whom understand the exercise prescription. By integrating care, slowing disease progression, and incorporating specialized rehabilitation we anticipate improving healthspan. In creating the IPU as a fully capitated (shared-risk) model in which the IPU and the insurance company assume joint accountability for quality and cost of care we anticipate demonstrating financial sustainability of implementing the exercise prescription and providing integrated care.